2017
DOI: 10.1002/14651858.cd011279.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and exercise for chronic pain in adults: an overview of Cochrane Reviews

Abstract: BackgroundChronic pain is defined as pain lasting beyond normal tissue healing time, generally taken to be 12 weeks. It contributes to disability, anxiety, depression, sleep disturbances, poor quality of life, and healthcare costs. Chronic pain has a weighted mean prevalence in adults of 20%.For many years, the treatment choice for chronic pain included recommendations for rest and inactivity. However, exercise may have specific benefits in reducing the severity of chronic pain, as well as more general benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
297
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(321 citation statements)
references
References 138 publications
16
297
2
6
Order By: Relevance
“…Our findings regarding the underlying mechanisms for why pain leads to falls have significant public health implications given the large proportion of older people who report pain and the high cost of fall-related injuries [6]. Relevant strategies for preventing falls in people with knee pain would include treating and managing pain, which may be through appropriate medication prescription, pain management and exercise [39,40]. The role of exercise in this regard may be particularly beneficial as targeted exercise can alleviate pain, reduce body weight as well as improve muscle strength and balance [39,40] two mediators for the relationship between pain and falls identified in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding the underlying mechanisms for why pain leads to falls have significant public health implications given the large proportion of older people who report pain and the high cost of fall-related injuries [6]. Relevant strategies for preventing falls in people with knee pain would include treating and managing pain, which may be through appropriate medication prescription, pain management and exercise [39,40]. The role of exercise in this regard may be particularly beneficial as targeted exercise can alleviate pain, reduce body weight as well as improve muscle strength and balance [39,40] two mediators for the relationship between pain and falls identified in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that symptoms and functional problems cause pain and discomfort that impair daily living over a long time. The adverse effects of chronic pain and discomfort on long-term anxiety and depression are well established 37 and will need to be treated with support and therapeutic programs. 38,39 In terms of clinical implications, the focus of attention during follow-up should be on preparing patients to better understand and cope with symptoms and functional problems.…”
Section: Research and Clinical Implicationsmentioning
confidence: 99%
“…Non-specific low back pain is one of the most common chronic pain conditions (Balagu e et al, 2012), and exercise of the low back has been shown to be an effective physical therapy (Shi et al, 2018). Exercise and other forms of physical therapy are approved therapeutic treatment strategies in the rehabilitation of patients suffering from chronic pain including low back pain (Heneweer et al, 2009;Hooten et al, 2012;Babatunde et al, 2017;Geneen et al, 2017). Physical therapy reduces pain reactions in animals (Cobianchi et al, 2010;Shen et al, 2013;Sluka et al, 2013;Santos et al, 2014;Lima et al, 2017) and pain in humans (Naugle et al, 2012;Babatunde et al, 2017).…”
Section: Introductionmentioning
confidence: 99%